Hesperetin Nanoparticle Targeting Neutrophils for Enhanced TBI Therapy. (8th August 2022) - Yao, Kai; Mu, Qingchun; Zhang, Yufei; Cheng, Qian; Cheng, Xiaozhi; Liu, Xiaojing; Luo, Chunmei; Li, Chumei; Cai, Shuxia; Luo, Zhicheng; Zhu, Xiulong; Zhang, Xiangtong; et al.
Abstract: Traumatic brain injury (TBI) is the main cause of death and disability in people of all ages worldwide. Neuroinflammation plays beneficial and harmful roles in secondary brain injury. Neutrophils play an important role in chemically mediated inflammatory responses through myeloperoxidase (MPO) and inflammation triggered by TBI. Herein, a nanodrug targeting neutrophils and MPO through chemical and biological functions after TBI is designed to enhance the retention and sustained release of drug cargos for improved TBI therapy. 5‐Hydroxytryptamide (5‐HT) is modified on nanoparticles (NPs) loaded with an anti‐inflammatory and antioxidant natural product, hesperetin, to obtain MPO‐ and neutrophil‐targeting NPs, denoted as T‐Hes. In a mouse TBI model, it is confirmed that neutrophil‐targeting NPs can quickly accumulate and remain in the brain tissue, reduce the secretion of inflammatory factors, and the level of microglia and astrocytes, subsequently inducing the transformation of microglia from pro‐inflammatory M1 to anti‐inflammatory M2 cells and promoting the infiltration of regulatory T cells (Tregs). T‐Hes significantly inhibits neuroinflammation and improves neurological deficits through the sustained release of hesperetin in the brain. The findings may open up new avenues for designing clinically translatable probes for TBI treatment. Abstract : A hesperetin nanoparticle that targets neutrophils, T‐Hes, catalyzed by MPO secreted by neutrophil is rationally designed. The T‐Hes can effectively identify inflammatory neutrophils and quickly gather in the injured area after TBI. The sustained release of hesperetin by T‐Hes shows great advantages in anti‐inflammatory treatment, reducing brain edema, and improving neurological function.